Reading courseware for Down syndrome and Hyperactive students (Bahasa Malaysia) - Talib, Nuriman (Universiti Teknologi PETRONAS, 2009)
This report presents the idea of developing and designing a courseware for Down syndrome and Hyperactive students. The courseware with title "Man Membaca" will be a kit for teachers and assist disabled student to improve their reading skill specifically on Bahasa Malaysia subject. The idea of the courseware is to give effective learning environment to disabled student (Down syndrome and Hyperactive) and optimize their learning ability. The reading courseware ispotentially to be developed by using Adobe Flash. The special remedial school syllabus is provided by Special Education Department, Ministry of Education is applied in the courseware. By using this courseware, students will experience to play educational games, training and exercise. To overcome reading disability, three techniques (Sound-symbol correspondence, word retrieval andvocabulary) is applied in the courseware. Forfurther enhancement, theproject need to be analyzed through user feedback from teacher and also disabled student. The Prototyping methodology used for this project is divided into several phases which include planning, analysis, design, prototype implementation, courseware prototype and implementation. Based on recommendation from Sekolah Kebangsaan Pengkalan Pegoh teachers, courseware is a potential learning tools for disabled student because they can interact with the courseware. The new learning environment could be beneficial for disabled student through the use of computer technology.